A lithium lanthanum zirconium oxide-based solid electrolyte material, a preparation method and a solid-state battery

CN116487688BActive Publication Date: 2026-10-27SHANDONG MAOHUA NEW ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310681646.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2026-10-27
Estimated Expiration
2043-06-09

AI Technical Summary

Benefits of technology

[0059]本发明针对传统固相法合成锂镧锆氧固态电解质时所需温度高、成本大的缺点,提供了一种合成温度≤900℃的固相法,不仅降低了合成温度和成本,而且解决了高温烧结过程中锂元素因高温而流失的问题,提高了锂镧锆氧在固态电池中的应用,促进了固态电池的发展。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116487688B_ABST
    Figure CN116487688B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of lithium lanthanum zirconium oxygen-based solid electrolyte material, preparation method and solid battery.The preparation method includes: after the metal oxide synthesized by calcination method is mixed with lithium source by wet method, low-temperature calcination is carried out under the condition of ≤900 ℃, and the lithium lanthanum zirconium oxygen-based solid electrolyte material is obtained;The metal oxide includes lanthanum oxide and zirconium oxide.For the shortcomings that the temperature required when synthesizing lithium lanthanum zirconium oxygen solid electrolyte by traditional solid phase method is high and cost is large, a solid phase synthesis method with synthesis temperature ≤900 ℃ is provided, which not only reduces the synthesis temperature and cost, but also solves the problem of lithium loss due to high temperature in the high-temperature sintering process, improves the application of lithium lanthanum zirconium oxygen in solid-state battery, and promotes the development of solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid electrolyte material manufacturing technology, and relates to a lithium lanthanum zirconium oxy-based solid electrolyte material, its preparation method, and a solid battery. Background Technology

[0002] With the increasing global consumption of fossil fuels such as oil, coal, and natural gas, energy depletion and environmental degradation pose serious challenges to humanity. Developing renewable energy storage and conversion is crucial for addressing these challenges. Among various energy storage systems, lithium-ion batteries are widely used in electronic products and electric vehicles due to their high energy density, long cycle life, and environmental friendliness. However, factors such as overcharging, electrolyte decomposition, self-discharge, and temperature cause lithium-ion battery capacity decay. Furthermore, the liquid electrolyte used in traditional commercial lithium-ion batteries poses flammable and explosive risks, and their energy density is approaching its limit of 300 Wh / kg. -1 The limitations of liquid electrolytes in energy storage, particularly in terms of energy density, have severely hampered their practical application. Meanwhile, solid-state electrolytes, with their enhanced safety, non-flammability, and wider electrochemical window, can effectively replace liquid electrolytes, thus solving these problems and improving the energy density of all-solid-state lithium batteries.

[0003] Among numerous solid-state electrolytes, cubic garnet-type solid-state electrolytes stand out due to their high ionic conductivity, chemical / electrochemical stability with lithium metal, and wide electrochemical window, attracting considerable attention from researchers. In 2003, Thangadurai et al. reported that, based on Li5La3M2O 12 (M=Nb,Ta) cubic garnet-type Li + The conductor is stable when reacting with molten lithium, but its ionic conductivity is only 10 at room temperature. -6 S cm -1 The cubic garnet Li7La3Zr2O discovered in 2007 12 The ionic conductivity is relatively high, at 10. -4 S cm -1 Subsequently, researchers conducted extensive studies on lithium lanthanum zirconium oxide solid electrolytes.

[0004] Lithium lanthanum zirconium oxide is typically synthesized using solid-state reactions, such as the reaction of LiOH or Li₂CO₃, La₂O₃, and ZrO₂, but this requires high temperatures (>1200℃) and long calcination times (e.g., 36 h). Lithium lanthanum zirconium oxide exists in two crystalline forms, with Li₂... + The electrical conductivity differs by 2-3 orders of magnitude. The tetragonal lithium-lanthanum-zirconium oxide phase is thermodynamically stable at room temperature, typically exhibiting a conductivity of 10-1. -7 ~10 -6 S cm-1 The cubic structure of lithium lanthanum zirconium oxide exhibits high ionic conductivity (10 Ω·cm). -4 S cm -1 ).

[0005] The vigorous development of low-temperature synthesis methods for lithium, lanthanum, and zirconium oxide is partly motivated by the need to avoid the high calcination temperatures required for solid-state synthesis, which would lead to the deterioration of Li... + Volatilization loss. The commonly used low-temperature synthesis method is the sol-gel method. In the solid-state method, elemental doping can reduce the sintering temperature to a certain extent, but its main function is to stabilize the cubic phase structure.

[0006] The solid-state synthesis of lithium lanthanum zirconium oxide (LLN) involves multiple ball milling and heat treatment processes, resulting in high costs. The sol-gel method is relatively complex and uses expensive raw materials, making it unsuitable for large-scale production. Therefore, providing a simple and low-cost low-temperature synthesis method is an urgent technical problem to be solved. Summary of the Invention

[0007] In view of the problems existing in the prior art, the present invention provides a lithium lanthanum zirconium oxide solid electrolyte material, a preparation method and a solid battery. Addressing the shortcomings of traditional solid-state synthesis of lithium lanthanum zirconium oxide solid electrolytes, which requires high temperatures and incurs high costs, this invention provides a solid-state synthesis method with a synthesis temperature ≤900℃. This not only reduces the synthesis temperature and cost but also solves the problem of lithium loss due to high temperatures during high-temperature sintering, thereby improving the application of lithium lanthanum zirconium oxide in solid-state batteries and promoting the development of solid-state batteries.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a method for preparing a lithium lanthanum zirconium oxy-based solid electrolyte material, the method comprising:

[0010] The metal oxide synthesized by calcination method is wet-mixed with a lithium source and then calcined at a low temperature of ≤900℃ to obtain the lithium lanthanum zirconium oxide solid electrolyte material.

[0011] The metal oxides include lanthanum oxide and zirconium oxide.

[0012] This invention addresses the drawbacks of traditional solid-state methods for synthesizing lithium lanthanum zirconium oxide solid electrolytes, which require high temperatures and incur high costs. It provides a solid-state method with a synthesis temperature ≤900℃, which not only reduces the synthesis temperature and cost but also solves the problem of lithium loss due to high temperatures during sintering. This improves the application of lithium lanthanum zirconium oxide in solid-state batteries and promotes the development of solid-state batteries.

[0013] Preferably, the method for synthesizing metal oxides by calcination includes: mixing a metal source and ammonia water to obtain a hydroxide precipitate, and then calcining it to obtain the metal oxide.

[0014] Preferably, the metal source includes a lanthanum source and a zirconium source.

[0015] Preferably, the lanthanum source includes any one or a combination of at least two of lanthanum oxide, lanthanum carbonate, lanthanum nitrate, or lanthanum chloride. Typical but non-limiting combinations include combinations of lanthanum oxide and lanthanum carbonate, lanthanum carbonate and lanthanum nitrate, lanthanum nitrate and lanthanum chloride, lanthanum oxide and lanthanum nitrate, lanthanum carbonate and lanthanum chloride, and lanthanum oxide and lanthanum chloride.

[0016] Preferably, the zirconium source includes any one or a combination of at least two of zirconium oxide, zirconium carbonate, zirconium nitrate, zirconium chloride, or zirconium oxychloride octahydrate. Typical but non-limiting combinations include combinations of zirconium oxide and zirconium carbonate, combinations of zirconium carbonate and zirconium nitrate, combinations of zirconium nitrate and zirconium oxychloride octahydrate, combinations of zirconium oxide and zirconium nitrate, combinations of zirconium oxide and zirconium oxychloride octahydrate, and combinations of zirconium carbonate and zirconium oxychloride octahydrate.

[0017] The lanthanum oxide and zirconium oxide used as lanthanum and zirconium sources, respectively, are different from the lanthanum oxide and zirconium oxide synthesized by calcination in this invention. They have a particle size of conventional micrometers or larger, or are crystalline lanthanum oxide and zirconium oxide, and do not have the characteristic of high reactivity.

[0018] Preferably, the ammonia water is in excess of 5-40%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0019] The term "excess" refers to an excess of molar amount relative to the stoichiometric ratio of the chemical reaction, for example:

[0020] La(NO3)3·6H2O+3NH3·H2O→La(OH)3↓+3NH4NO3+9H2O

[0021] 1 mol of La(NO3)3·6H2O requires 3 mol of NH3·H2O, with an excess of 5-40% mol on top of the 3 mol.

[0022] Preferably, the calcination temperature is 500-800℃, for example, 500℃, 550℃, 600℃, 650℃, 700℃, or 750℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0023] Preferably, the metal oxide is in the form of nanoscale particles.

[0024] This invention obtains nanoscale lanthanum oxide and zirconium oxide through calcination. These materials have poor crystallinity and high reactivity. When mixed with a lithium source as raw materials, they can effectively reduce the calcination temperature required for the synthesis of materials.

[0025] Preferably, the wet mixing method is as follows: ball milling and mixing the metal oxide, lithium source and organic solvent, followed by drying.

[0026] Preferably, the lithium source includes lithium hydroxide and / or lithium carbonate.

[0027] Preferably, the molar excess of the lithium source is 5-20%, for example, it can be 5%, 10%, 15%, 18% or 20%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0028] The amounts of lanthanum oxide, zirconium oxide, and lithium source are prepared according to the chemical dosage ratio of lithium, lanthanum, zirconium oxide, and oxy group, wherein the excess lithium source is to compensate for the volatilization of lithium during calcination.

[0029] Preferably, the organic solvent comprises any one or a combination of at least two of isopropanol, propanol, ethanol, methylpyrrolidone, toluene, acetone, n-butanol, or dimethylformamide. Typical but non-limiting combinations include combinations of isopropanol and propanol, propanol and ethanol, ethanol and methylpyrrolidone, methylpyrrolidone and toluene, toluene and acetone, acetone and n-butanol, and n-butanol and dimethylformamide.

[0030] Preferably, the rotational speed of the ball mill is 100 to 800 r / min, for example, it can be 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min, or 800 r / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0031] Preferably, the ball milling time is 6 to 72 hours, for example, 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, 48 ​​hours, 54 hours, 60 hours, 66 hours, or 72 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0032] Preferably, the ball mill includes a planetary ball mill and / or a high-energy ball mill.

[0033] Preferably, the drying temperature is -20 to 80°C, for example, it can be -20°C, -10°C, 0°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, or 80°C, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0034] Preferably, the drying time is 6 to 36 hours, for example, 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, or 36 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0035] Preferably, the drying equipment includes any one or a combination of at least two of the following: a vacuum dryer, a vacuum oven, or a freeze dryer.

[0036] Preferably, the powder obtained after wet mixing is pressed.

[0037] Preferably, the pressing pressure is 10 to 200 MPa, for example, it can be 10 MPa, 50 MPa, 100 MPa, 150 MPa or 200 MPa, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0038] Preferably, the pressing is in the form of a disc.

[0039] After pressing, the dispersed powder is tightly distributed in space, which promotes the reaction and helps to reduce the temperature required for calcination.

[0040] Preferably, the low-temperature calcination temperature is 650-900℃, for example, it can be 650℃, 700℃, 750℃, 800℃, 850℃, or 900℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0041] Preferably, the heating rate of the low-temperature calcination is 1 to 5 °C / min, for example, it can be 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, or 5 °C / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0042] Preferably, the holding time for the low-temperature calcination is 6 to 36 hours, for example, 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, or 36 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0043] Preferably, the annealing rate of the low-temperature calcination is 1 to 5 °C / min, for example, it can be 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, or 5 °C / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0044] Preferably, the process after low-temperature calcination further includes mechanical crushing.

[0045] Preferably, the mechanical crushing machine includes any one or a combination of at least two of the following: an air jet mill, a planetary ball mill, a vertical sand mill, a horizontal ball mill, or a high-energy ball mill. Typical but non-limiting combinations include a combination of an air jet mill and a planetary ball mill, a combination of a planetary ball mill and a vertical sand mill, a combination of a vertical sand mill and a horizontal ball mill, and a combination of a horizontal ball mill and a high-energy ball mill.

[0046] Preferably, the operating speed of the mechanical crusher is 100-800 r / min, for example, it can be 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min, or 800 r / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0047] Preferably, the working time of the mechanical crushing is 6 to 72 hours, for example, it can be 6 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, 48 ​​hours, 54 hours, 60 hours, 66 hours, or 72 hours, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0048] As a preferred embodiment of the preparation method described in the first aspect of the present invention, the preparation method includes:

[0049] (1) Synthesis of lanthanum oxide and zirconium oxide by calcination: Lanthanum source and excess ammonia water of 5-40% are mixed to obtain lanthanum hydroxide precipitate, which is then calcined at 500-800℃ to obtain lanthanum oxide; Zirconium source and excess ammonia water of 5-40% are mixed to obtain zirconium hydroxide precipitate, which is then calcined at 500-800℃ to obtain zirconium oxide;

[0050] (2) Lanthanum oxide, lithium zirconium oxide and organic solvent were ball-milled at a speed of 100-800 r / min for 6-72 h, and then dried at -20-80℃ for 6-36 h to obtain powder.

[0051] (3) The obtained powder is pressed into a disc shape under a pressure of 10-200 MPa, and then calcined at a low temperature of 650-900℃. The heating rate of the low temperature calcination is 1-5℃ / min, the holding time is 6-36h, the annealing rate is 1-5℃ / min, and the calcined material is mechanically crushed at a working speed of 100-800 r / min for 6-72h to obtain the lithium lanthanum zirconium oxide solid electrolyte material.

[0052] In a second aspect, the present invention provides a lithium lanthanum zirconium oxy-based solid electrolyte material, which is obtained by the preparation method described in the first aspect.

[0053] Preferably, the lithium lanthanum zirconium oxide solid electrolyte material is a nanoscale powder material.

[0054] Preferably, the particle size range of the lithium lanthanum zirconium oxide solid electrolyte material is 50 to 500 nm, for example, it can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0055] Preferably, the lithium lanthanum zirconium oxide solid electrolyte material is a cubic phase powder.

[0056] The preparation method of this invention yields nanoscale lithium lanthanum zirconium oxy-based solid electrolyte materials with grain sizes ranging from 50 to 500 nm. These cubic phase powders exhibit good phase uniformity and can be composited with polymers to obtain composite electrolytes. This allows for the preparation of flexible solid electrolytes with thicknesses within tens of micrometers, thereby promoting the application of solid-state batteries. Furthermore, the obtained lithium lanthanum zirconium oxy-based solid electrolyte material possesses high ionic conductivity and can be used as an electrolyte in all-solid-state batteries, significantly improving battery safety.

[0057] Thirdly, the present invention provides a solid-state battery containing a lithium lanthanum zirconium oxide solid electrolyte material as described in the second aspect.

[0058] Based on the above technical solutions, the beneficial effects of the present invention are as follows:

[0059] This invention addresses the drawbacks of traditional solid-state methods for synthesizing lithium lanthanum zirconium oxide solid electrolytes, which require high temperatures and incur high costs. It provides a solid-state method with a synthesis temperature ≤900℃, which not only reduces the synthesis temperature and cost but also solves the problem of lithium loss due to high temperatures during sintering. This improves the application of lithium lanthanum zirconium oxide in solid-state batteries and promotes the development of solid-state batteries.

[0060] The preparation method of this invention yields nanoscale lithium lanthanum zirconium oxy-based solid electrolyte materials with grain sizes ranging from 50 to 500 nm. These cubic phase powders exhibit good phase uniformity and can be composited with polymers to obtain composite electrolytes. This allows for the preparation of flexible solid electrolytes with thicknesses within tens of micrometers, thereby promoting the application of solid-state batteries. Furthermore, the obtained lithium lanthanum zirconium oxy-based solid electrolyte material possesses high ionic conductivity and can be used as an electrolyte in all-solid-state batteries, significantly improving battery safety. Attached Figure Description

[0061] Figure 1 This is the XRD pattern of lanthanum oxide as described in Example 1.

[0062] Figure 2 This is the XRD pattern of the zirconium oxide described in Example 1.

[0063] Figure 3 This is the XRD pattern of the lithium lanthanum zirconium oxide solid electrolyte material described in Example 1.

[0064] Figure 4 This is a TEM image of the lithium lanthanum zirconium oxide solid electrolyte material described in Example 1. Detailed Implementation

[0065] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0066] Example 1

[0067] This embodiment provides a method for preparing a lithium lanthanum zirconium oxide solid electrolyte material, the preparation method comprising:

[0068] (1) Synthesis of lanthanum oxide and zirconium oxide by calcination: 0.1 mol of lanthanum nitrate and 0.3 mol of ammonia were dissolved in 100 ml of deionized water, and the two solutions were mixed to precipitate the lanthanum. Ammonia was added in excess by 30% to ensure that all lanthanum precipitated as lanthanum hydroxide. The resulting lanthanum hydroxide was calcined at 700℃ for 30 min to obtain lanthanum oxide (XRD as shown). Figure 1 (As shown); Weigh 0.1 mol of zirconium chloride and 0.4 mol of ammonia water, add 100 ml of deionized water respectively, and then mix the two solutions to precipitate. The ammonia water is in excess by 30% to ensure that all zirconium is precipitated as zirconium hydroxide. The zirconium hydroxide is calcined at 500℃ and held at that temperature for 30 min to obtain zirconium oxide (XRD as shown). Figure 2 (as shown);

[0069] (2) According to Li7La3Zr2O 12Lanthanum oxide, zirconium oxide, lithium hydroxide monohydrate (15% excess relative to the theoretical molar amount of lithium hydroxide calculated according to the chemical reaction equation), and isopropanol were mixed in a stoichiometric ratio and ball-milled for 12 hours at a speed of 600 r / min to achieve uniform mixing. After ball milling, the wet material was dried at 60°C for 12 hours to obtain powder.

[0070] (3) The obtained powder is ground and then pressed into tablets under a pressure of 10 MPa for 3 min, and then calcined at a low temperature of 800℃. The heating rate of the low temperature calcination is 5℃ / min, the holding time is 12 h, the annealing rate is 2℃ / min, and the calcined material is mechanically crushed at a working speed of 600 r / min for 12 h to obtain the lithium lanthanum zirconium oxide solid electrolyte material.

[0071] The XRD pattern of the lithium lanthanum zirconium oxide solid electrolyte material is as follows: Figure 3 As shown, a single-phase material was obtained. The lithium lanthanum zirconium oxide solid electrolyte material is a cubic phase nanoscale powder material with a particle size range of 50–500 nm. TEM results are shown below. Figure 2 As shown, the particle size of the prepared lithium lanthanum zirconium oxy-based solid electrolyte material is at the nanometer level.

[0072] Example 2

[0073] This embodiment provides a method for preparing a lithium lanthanum zirconium oxide solid electrolyte material, the preparation method comprising:

[0074] (1) Synthesis of lanthanum oxide and zirconium oxide by calcination: 0.5 mol of lanthanum chloride and 1.5 mol of ammonia water were weighed and dissolved in 200 ml of deionized water respectively. The two solutions were then mixed and precipitated, with 20% excess ammonia water to ensure that all lanthanum was precipitated as lanthanum hydroxide. The obtained lanthanum hydroxide was calcined at 750 °C and kept at that temperature for 60 min to obtain lanthanum oxide. 0.5 mol of zirconium oxychloride octahydrate and 2.0 mol of ammonia water were weighed and dissolved in 50 ml of deionized water respectively. The two solutions were then mixed and precipitated, with 20% excess ammonia water to ensure that all zirconium was precipitated as zirconium hydroxide. The zirconium hydroxide was calcined at 550 °C and kept at that temperature for 60 min to obtain zirconium oxide.

[0075] (2) According to Li7La3Zr2O 12 Lanthanum oxide, zirconium oxide, lithium carbonate (10% excess relative to the theoretical molar amount of lithium carbonate calculated according to the chemical reaction equation), and methylpyrrolidone were mixed in stoichiometric ratio and ball-milled for 8 hours at a speed of 650 r / min to achieve uniform mixing. After ball milling, the wet material was dried at 70°C for 10 hours to obtain powder.

[0076] (3) The obtained powder is ground and then pressed into tablets under a pressure of 10 MPa for 3 min, and then calcined at a low temperature of 850℃. The heating rate of the low temperature calcination is 2℃ / min, the holding time is 24 h, the annealing rate is 2℃ / min, and the calcined material is mechanically crushed at a working speed of 700 r / min for 24 h to obtain the lithium lanthanum zirconium oxide solid electrolyte material.

[0077] The lithium lanthanum zirconium oxide solid electrolyte material is a cubic phase nanoscale powder material with a particle size range of 200–500 nm.

[0078] Example 3

[0079] This embodiment provides a method for preparing a lithium lanthanum zirconium oxide solid electrolyte material, the preparation method comprising:

[0080] (1) Synthesis of lanthanum oxide and zirconium oxide by calcination: 0.2 mol of lanthanum carbonate and 0.6 mol of ammonia water were weighed and dissolved in 100 ml of deionized water respectively. The two solutions were then mixed and precipitated, with 40% excess ammonia water to ensure that all lanthanum was precipitated as lanthanum hydroxide. The obtained lanthanum hydroxide was calcined at 750℃ and kept at that temperature for 90 min to obtain lanthanum oxide. 0.2 mol of zirconium nitrate and 0.8 mol of ammonia water were weighed and dissolved in 100 ml of deionized water respectively. The two solutions were then mixed and precipitated, with 40% excess ammonia water to ensure that all zirconium was precipitated as zirconium hydroxide. The zirconium hydroxide was calcined at 550℃ and kept at that temperature for 90 min to obtain zirconium oxide.

[0081] (2) According to Li7La3Zr2O 12 Lanthanum oxide, zirconium oxide, lithium hydroxide monohydrate (20% excess relative to the theoretical molar amount of lithium hydroxide monohydrate calculated according to the chemical reaction equation), and acetone were mixed in a stoichiometric ratio and ball-milled for 8 hours at a speed of 800 r / min to achieve uniform mixing. After ball milling, the wet material was dried at 80℃ for 6 hours to obtain powder.

[0082] (3) The obtained powder is ground and then pressed into tablets under a pressure of 10 MPa for 3 min, and then calcined at a low temperature of 800℃. The heating rate of the low temperature calcination is 3℃ / min, the holding time is 18 h, the annealing rate is 3℃ / min, and the calcined material is mechanically crushed at a working speed of 700 r / min for 24 h to obtain the lithium lanthanum zirconium oxide solid electrolyte material.

[0083] The lithium lanthanum zirconium oxide solid electrolyte material is a cubic phase nanoscale powder material with a particle size range of 100–500 nm.

[0084] Example 4

[0085] This embodiment provides a method for preparing a lithium lanthanum zirconium oxide solid electrolyte material, which differs from Example 1 in that the ammonia water in step (1) is not excessive.

[0086] The prepared lithium lanthanum zirconium oxide solid electrolyte material has an inhomogeneous phase.

[0087] Example 5

[0088] This embodiment provides a method for preparing a lithium lanthanum zirconium oxy-based solid electrolyte material. The difference from Embodiment 1 is that the lithium hydroxide monohydrate in step (2) is not excessive.

[0089] The prepared lithium lanthanum zirconium oxide solid electrolyte material has an inhomogeneous phase.

[0090] Example 6

[0091] This embodiment provides a method for preparing a lithium lanthanum zirconium oxide solid electrolyte material, which differs from Example 1 in that step (3) does not involve tableting.

[0092] The prepared lithium lanthanum zirconium oxide solid electrolyte material has an inhomogeneous phase.

[0093] Example 7

[0094] This embodiment provides a method for preparing a lithium lanthanum zirconium oxy-based solid electrolyte material. The difference from Example 1 is that the calcination temperature in step (3) is 600℃.

[0095] The preparation method described in the embodiment cannot obtain the phase of the lithium lanthanum zirconium oxide solid electrolyte material.

[0096] Comparative Example 1

[0097] This comparative example provides a method for preparing a lithium lanthanum zirconium oxide-based solid electrolyte material. The difference from Example 1 is that lanthanum oxide and zirconium oxide are not synthesized by calcination, but are replaced by conventional micron-sized lanthanum oxide and zirconium oxide.

[0098] The preparation method described in the embodiment cannot obtain the phase of the lithium lanthanum zirconium oxide solid electrolyte material.

[0099] Comparative Example 2

[0100] This comparative example provides a method for preparing a lithium lanthanum zirconium oxy-based solid electrolyte material, which differs from Example 1 in that the calcination temperature is 1000℃.

[0101] The lithium volatilization rate is high during the preparation process, resulting in a low lithium content in the lithium lanthanum zirconium oxide solid electrolyte material.

[0102] The lithium lanthanum zirconium oxide solid electrolyte material obtained above was used as the electrolyte, lithium sheet as the negative electrode, and lithium iron phosphate positive electrode as the positive electrode. Following the assembly sequence of coin cell lithium-ion batteries, an all-solid-state battery was assembled and tested. The test method was to measure the AC impedance by blocking the electrodes and calculate the ionic conductivity. The test results are shown in Table 1.

[0103] Table 1

[0104]

[0105]

[0106] In summary, this invention addresses the drawbacks of traditional solid-state methods for synthesizing lithium lanthanum zirconium oxide solid electrolytes, which require high temperatures and incur high costs. It provides a solid-state method with a synthesis temperature ≤900℃, which not only reduces the synthesis temperature and cost but also solves the problem of lithium loss due to high temperatures during sintering. This improves the application of lithium lanthanum zirconium oxide in solid-state batteries and promotes the development of solid-state batteries.

[0107] The preparation method of this invention yields nanoscale lithium lanthanum zirconium oxy-based solid electrolyte materials with grain sizes ranging from 50 to 500 nm. These cubic phase powders exhibit good phase uniformity and can be composited with polymers to obtain composite electrolytes. This allows for the preparation of flexible solid electrolytes with thicknesses within tens of micrometers, thereby promoting the application of solid-state batteries. Furthermore, the obtained lithium lanthanum zirconium oxy-based solid electrolyte material possesses high ionic conductivity and can be used as an electrolyte in all-solid-state batteries, significantly improving battery safety.

[0108] The present invention has been illustrated with the above embodiments to illustrate its detailed structural features. However, the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the components used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium lanthanum zirconium oxide solid electrolyte material, characterized in that, The preparation method includes: The metal oxide synthesized by calcination method is wet-mixed with a lithium source and then calcined at a low temperature of ≤900℃ to obtain the lithium lanthanum zirconium oxide solid electrolyte material. The method for synthesizing metal oxides by calcination includes: mixing a metal source and ammonia water to obtain a hydroxide precipitate, followed by calcination to obtain the metal oxide; wherein the ammonia water is in excess by 5-40%. The wet mixing method involves ball milling and mixing the metal oxide, lithium source, and organic solvent, followed by drying; the lithium source is in excess by 5-20% molar amount. The metal oxides include lanthanum oxide and zirconium oxide; the metal oxides are nanoscale particles.

2. The preparation method according to claim 1, characterized in that, The metal source includes a lanthanum source and a zirconium source.

3. The preparation method according to claim 2, characterized in that, The lanthanum source includes any one or a combination of at least two of lanthanum oxide, lanthanum carbonate, lanthanum nitrate, or lanthanum chloride.

4. The preparation method according to claim 2, characterized in that, The zirconium source includes any one or a combination of at least two of zirconium oxide, zirconium carbonate, zirconium nitrate, zirconium chloride, or zirconium oxychloride octahydrate.

5. The preparation method according to claim 1, characterized in that, The calcination temperature is 500~800℃.

6. The preparation method according to claim 1, characterized in that, The lithium source includes lithium hydroxide and / or lithium carbonate.

7. The preparation method according to claim 1, characterized in that, The organic solvent includes any one or a combination of at least two of isopropanol, propanol, ethanol, methylpyrrolidone, toluene, acetone, n-butanol, or dimethylformamide.

8. The preparation method according to claim 1, characterized in that, The ball mill rotates at a speed of 100~800 r / min.

9. The preparation method according to claim 1, characterized in that, The ball milling time is 6~72 hours.

10. The preparation method according to claim 1, characterized in that, The drying temperature is -20~80℃.

11. The preparation method according to claim 1, characterized in that, The drying time is 6 to 36 hours.

12. The preparation method according to claim 1, characterized in that, The powder obtained after wet mixing is then pressed.

13. The preparation method according to claim 12, characterized in that, The pressing pressure is 10~200MPa.

14. The preparation method according to claim 12, characterized in that, The material is pressed into a circular sheet shape.

15. The preparation method according to claim 1, characterized in that, The temperature for the low-temperature calcination is 650~900℃.

16. The preparation method according to claim 1, characterized in that, The heating rate for the low-temperature calcination is 1~5℃ / min.

17. The preparation method according to claim 1, characterized in that, The holding time for the low-temperature calcination is 6~36h.

18. The preparation method according to claim 1, characterized in that, The annealing rate for the low-temperature calcination is 1~5℃ / min.

19. The preparation method according to claim 1, characterized in that, The process after low-temperature calcination also includes mechanical crushing.

20. The preparation method according to claim 19, characterized in that, The mechanical crushing machine includes any one or a combination of at least two of the following: air jet mill, planetary ball mill, vertical sand mill, horizontal ball mill, or high-energy ball mill.

21. The preparation method according to claim 19, characterized in that, The mechanical crusher operates at a speed of 100~800 r / min.

22. The preparation method according to claim 19, characterized in that, The mechanical crushing process takes 6 to 72 hours.

23. The preparation method according to claim 1, characterized in that, The preparation method includes: (1) Synthesis of lanthanum oxide and zirconium oxide by calcination: Lanthanum source and excess ammonia water of 5-40% are mixed to obtain lanthanum hydroxide precipitate, which is then calcined at 500-800℃ to obtain lanthanum oxide; Zirconium source and excess ammonia water of 5-40% are mixed to obtain zirconium hydroxide precipitate, which is then calcined at 500-800℃ to obtain zirconium oxide; (2) Lanthanum oxide, lithium zirconium oxide and organic solvent are ball-milled at a speed of 100~800 r / min for 6~72 h, and then dried at -20~80℃ for 6~36 h to obtain powder. (3) The obtained powder is pressed into a disc shape under a pressure of 10~200MPa, and then calcined at a low temperature of 650~900℃. The heating rate of the low temperature calcination is 1~5℃ / min, the holding time is 6~36h, the annealing rate is 1~5℃ / min, and the calcined material is mechanically crushed at a working speed of 100~800r / min for 6~72h to obtain the lithium lanthanum zirconium oxide solid electrolyte material.

24. A lithium lanthanum zirconium oxide solid electrolyte material, characterized in that, The lithium lanthanum zirconium oxide solid electrolyte material is obtained by the preparation method described in any one of claims 1-23.

25. The lithium lanthanum zirconium oxide solid electrolyte material according to claim 24, characterized in that, The lithium lanthanum zirconium oxide solid electrolyte material is a nanoscale powder material.

26. The lithium lanthanum zirconium oxide solid electrolyte material according to claim 24, characterized in that, The particle size range of the lithium lanthanum zirconium oxide solid electrolyte material is 50~500 nm.

27. The lithium lanthanum zirconium oxide solid electrolyte material according to claim 24, characterized in that, The lithium lanthanum zirconium oxide solid electrolyte material is a cubic phase powder.

28. A solid-state battery, characterized in that, The solid-state battery contains the lithium lanthanum zirconium oxide solid electrolyte material as described in any one of claims 24-27.

Citation Information

Patent Citations

  • Erbium-doped cubic phase garnet type solid electrolyte material and synthesis method thereof

    CN110444805A

  • Pure cubic phase nanometer lithium gallium lanthanum zirconium oxide powder and preparation method and application thereof

    CN114361577A